KETERAMPILAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PENGELOLAAN KELAS DI SMP NEGERI 2 RAO UTARA KABUPATEN PASAMAN - Hilmi Hilmi (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: A teacher is expected to be capable and professional in the field of education, one of which is in terms of classroom management during the learning process. To manage this, good teacher management is needed, because classroom management is an effort to create and maintain optimal conditions in order for an effective learning process to occur. Based on the results of research in SMP 2 Rao Utara, Islamic Religious Education Teachers (PAI) are still less skilled in managing a good class of skills related to the creation and maintenance of optimal (preventive) learning conditions and skills related to the optimal return of learning conditions ( curative). This can be seen from the lack of classroom management components implemented such as the lack of teacher responsiveness in terms of looking at students carefully, during the learning process the teacher always looks at the student as a whole, but when students do the assignment the teacher gives less attention to students so the class is not conducive. Keywords: PAI Teacher Skills, Class Management